Different Ways of Teaching Grammar (Eurasian Journal of Humanities and Social Sciences, 2023)
It has long been believed that teaching grammar is essential for developing language skills. This article presents a five-step method for teaching grammar as a result. This method, which I created, combines explicit and implicit knowledge, deductive and inductive techniques to teaching grammar, as well as the concepts of practice and consciousness-raising. This method emerged from my keen interest in creative grammar instruction and my experience as a grammar teacher. The suggested actions are anticipated to provide English instructors with an alternate route for instructing grammar, particularly when it comes to teaching tenses and modals at college and university levels or even in lower schools.